The Russian - Patterson, James, 1947-; Born, James O. (Little, Brown and Company, 2021)
A serial killer crashes Detective Michael Bennett$1 (Bs wedding. Weeks before NYPD Detective Michael Bennett is to marry his longtime love, Mary Catherine, an assassin announces his presence in the city with a string of grisly murders. Each victim is a young woman. And each has been killed in a manner as precise as it was gruesome.--Amazon.com.s
Keywords: Bennett, Michael -- (Fictitious character) -- Fiction; Serial murder investigation -- Fiction; Detective and mystery stories; Thrillers (Fiction).; Novels; Detective and mystery fiction